Perioperative complications of laparoscopic inguinal hernia repair in India: a prospective observational study - Vikram Saini; Amrutha Varshini R; Yashwant Singh Rathore; Sunil Chumber; Kamal Kataria; Richa Garg (Journal of Minimally Invasive Surgery)
Purpose: These days laparoscopic inguinal hernia surgery, both totally extraperitoneal (TEP) and transabdominal preperitoneal (TAPP), is a commonly performed procedure due to advancements in laparoscopic instruments and the availability of skilled laparoscopic surgeons. The purpose of this study was to compare the perioperative complications of these two procedures. Methods : This was a prospective observational study between July 2019 and December 2020. Perioperative complications were compared with a 6-month follow-up. It included 144 patients, of whom 71 underwent TAPP repair and 73 underwent TEP repair. The selection was based on the surgeon’s choice. Results : Early postoperative complications were scrotal edema (12 cases in TEP and 16 in TAPP), urinary retention (one case in TEP), ecchymosis (six cases in TEP and two in TAPP), and scrotal subcutaneous emphysema (two cases in TEP). On follow-up, seroma was found in a total of 22 cases, of which 12 were TEP and 10 were TAPP. While only one case of TAPP developed surgical site infection. There was no statistically significant difference in hospital stay between the two groups (p = 0.58). The pain scores significantly decreased throughout recovery and were comparable between the groups. Neither group experienced a recurrence during the 6-month follow-up. Fifty-eight patients developed Clavien-Dindo grade I complications, one had grade II, and three had grade IIIa complications. Conclusion : With the increasing experience of the surgical fraternity in laparoscopic surgery, TEP and TAPP were proven to be comparable in terms of duration of surgery, postoperative complications, hospital stay, pain scores, and recurrence during the 6-month follow-up.